IMPLEMENTATION OF AL-QURAN MEMORIZATION LEARNING MANAGEMENT IN ISLAMIC UNIVERSITIES - Harahap, Muhammad Sapii (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to describe the Implementation of Al-Qur'an Tahfidz Learning Management in Islamic Colleges, namely the As-Sunnah Islamic College of Deli Serdang. This study is a qualitative or field research using a phenomenological approach to learning Al-Qur'an tahfidz. The results of this study are that 1) The planning carried out by STAI As-Sunnah in learning Al-Qur'an tahfidz is a) Planning the Al-Qur'an Tahifidz Program, b) Planning the juz that is tahsinkan and memorized, c) Planning the schedule for implementing its activities, d) Planning student groups, e) Planning Muallim/mah for each group, f) Planning student assessments, g) Planning the place for learning Al-Qur'an tahfidz in each group, and h) Planning the part that controls the continuity of the Al-Qur'an tahfidz activities. 2) Organization, namely: a) Head of STAI As-Sunnah, b) Head of Markaz Qur'an STAI As-Sunnah, c) Members of Markaz Qur'an STAI As-Sunnah, d) Muallim and Muallimah Halaqoh Qur'an, and e) Students of STAI As-Sunnah, 3) Implementation, namely a) Implementing the Tahifidz Al-Qur'an Program, namely a) Tahsin Al-Qur'an Program, namely by listening to students to their respective Muallim/mah, and b) Tasmi' hafalan Al-Qura'n, namely students memorizing the Al-Qur'an to each of their Muallim/ah. b) Implementing the juz that has been tahsinned and memorized, namely: a) tahsin for semester 1 is juz 30, semester 2 is juz 29, semester 3 is juz 28, semester 4 is juz 27, semester 5 is juz 26, semester 6 is juz 1, and semester 7 is juz 2, and b) memorization that will be memorized by students is for semester 1 is juz 30, semester 2 is juz 29, semester 3 is juz 28, semester 4 is juz 27, semester 5 is juz 26, semester 6 is juz 1, and semester 7 is juz 2. In each meeting, students are required to read the Qur'an and listen to their memorization to their Muallim/ah 1 page with 20 meetings finishing 1 juz. c) Implementing the schedule of its activities, namely the implementation of Tahsin every Saturday and Monday after the Asyar prayer, namely at 16.15 WIB until 17.45 WIB, while the implementation of Tahfidz every Sunday and Wednesday after the Asyar prayer, namely at 16.15 WIB until 17.45 WIB. d) Determining the student groups, namely each student has two groups, namely the tahsin group and the tahfidz group and each group is made up of 12 students. e) Determining the Muallim/mah of each group, namely each Muallim/ah has two groups, namely the tahsin group and the tahfidz group. f) Determining the student assessment, namely each Muallim gives a score to the students he/she guides using the guide provided by Markaz Al-Qur'an. This assessment is carried out by the Muallim/ah at each meeting, namely meetings 1-20, while at meeting 21 it is the examiner who gives the score. In semester 8 all students are required to take the comprehensive exam of the Qur'an, namely 7 juz and must memorize and pass when tested by the examiner. g) Determining the place of learning the tahfidz of the Qur'an in each group, specifically for students, all group locations are at the Imam Syafii Mosque, which is a mosque located at the student's location, while for female students, all groups are in the prayer room of the STAI As-Sunnah female student environment with a circular or elongated shape. And h) Determining the part that controls the continuity of the tahfidz activities of the Qur'an. The part that controls this activity is the Markaz Tahfizd Al-Qur'an STAI As-Sunnah. 4) Evaluation of learning includes a form to evaluate the activities that have been planned and implemented. In this evaluation, two things are done, namely controlling activities and assessing the tahfidz program of the Qur'an.